2019
DOI: 10.1155/2019/9014641
|View full text |Cite
|
Sign up to set email alerts
|

Physical Modeling and Numerical Simulation of the Seismic Responses of Metro Tunnel near Active Ground Fissures

Abstract: Ground fissures pose serious hazards to underground, as well as aboveground, structures. In underground railways, which are near ground fissures, the potential for disasters is even higher since tunnels face threats from fissure activities. To determine the interaction between a tunnel and ground fissure in the event of an earthquake, field surveys and data analysis were applied to study the activity and damage caused by the fissure. Shaking table tests and a numerical simulation model were used to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Many scholars have researched the mechanism behind damage to tunnel-crossing faults and achieved relevant results [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For example, Mehdi Sabagh [14] conducted a 1:60 centrifuge test of a tunnel crossing an active normal fault, exploring the mechanism of tunnel failure and the process of crack development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many scholars have researched the mechanism behind damage to tunnel-crossing faults and achieved relevant results [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For example, Mehdi Sabagh [14] conducted a 1:60 centrifuge test of a tunnel crossing an active normal fault, exploring the mechanism of tunnel failure and the process of crack development.…”
Section: Introductionmentioning
confidence: 99%
“…Yang-Zhihua et al [17] concluded that seismic motion and faults can change the initial stress field of the tunnel surrounding rock, resulting in stress accumulation and stress concentration in the tunnel surrounding rock near the fault and, ultimately, progressive destruction. Liu-Nina et al [18] carried out shaking table model tests for a metro tunnel crossing active ground cracks. They studied the acceleration response, soil pressure, and strain variation of the metro tunnel under seismic action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of GFs is usually related to the effects of internal and external forces and human activity (Peng 2012;Lu et al 2013;Liu et al 2019b). As a geological disaster, GFs not only cause serious damage to various types of engineering structures, such as urban buildings, roads, bridges, and underground pipelines (Peng et al 2018;Liu et al 2019a), but also cause many environmental problems including groundwater system damage and the destruction of land (Howard and Zhou 2019). Because GF disasters are common in many countries worldwide, such as the United States, Saudi Arabia, and Mexico, GF formation mechanism and the factors affecting their development have received research attention (e.g., Jachens and Holzer 1982;Holzer 1984Holzer , 1991Bankher and Al-Harthi 1999;Wang et al 2009Wang et al , 2016Pacheco-Martínez et al 2013).…”
Section: Introductionmentioning
confidence: 99%